Model of a photovoltaic panel emulator in MATLAB-Simulink - Can, Hayrettin (Tubitak Scientific & Technological Research Council Turkey, 2013)
Being able to behave electrically similar to photovoltaic (PV) panels, PV emulator systems make it possible to perform different PV system tests under various operation conditions. In this paper, a model of a PV panel emulator is presented using the Power System Blockset under MATLAB-Simulink. The simulation of the emulator system is developed for testing a controller prior to a real-time implementation. The model can handle the dependence of all of the parameters in the model with respect to solar radiation and temperature. The simulation results show that the output characteristics of the simulator have good agreement with those of the actual PV panel in various load conditions. Additionally, the simulator has a good dynamic response.
Keywords: Circuit based; emulator; modeling; photovoltaic panel